Tuning the separation performance of hydrogen permeable membranes using an anion doping strategy. Issue 38 (21st September 2017) - Chen, Li; Zhuang, Libin; Xue, Jian; Wei, Yanying; Wang, Haihui
Abstract : Fluoride-anion doping is first reported for tuning the separation performance of mixed protonic-electronic conducting (MPEC) membranes, and enhanced hydrogen permeability was observed with appropriate introduction of the fluoride ions. Abstract : Overcoming the dilemma between hydrogen permeability and stability is critical for realizing the widespread application of mixed protonic–electronic conducting (MPEC) membranes. Herein, fluoride-anion doping is for the first time reported for tuning the separation performance of MPEC membranes. Lanthanum tungstate oxyfluoride membranes, La5.5 W0.6 Mo0.4 O11.25− δ F x ( x = 0, 0.025, 0.05, 0.10, 0.20, 0.50), exhibit improved hydrogen permeability and enhanced stability compared to their parent oxides, achieving a maximum value of 0.20 mL min −1 cm −2 at x = 0.05. Moreover, the declining hydrogen permeability performance of lanthanum tungstate MPEC membranes during high-temperature operation was systematically analyzed and relative solutions are put forward. The anion-doping and stability-improving strategies might accelerate the development and future practical applications of MPEC membranes.